Body-Representation and Sexual Identity Projections: A Survey of Advertising in Print Media - Dr. Haseeb Ur Rehman Warrich; Dr. Ayesha Qamar; Zil e Huma (Journal of Peace, Development and Communication, 2021)
Matrimonial advertisements provide an unobtrusive site where the image, construction and perpetuation of normative heterosexuality are observed through socio-cultural discourses. The current study focuses on self-representation and gender role expectations in 550 classified matrimonial ads from two popular newspapers (The Daily Dawn, The Daily Jang) in Pakistan. Gender differences in desirable physical attributes, occupational preferences and personality traits are examined. The results revealed that gender polarization in ideal spousal occupations, and the relative variability in gender identities of women as compared to men. A strong preference for pretty and slim women is observed. Implications for the sexual objectification of women and changing gender roles in changing socioeconomic landscape of Pakistan is due to the impact of globalization.